Base editing‐mediated perturbation of endogenous PKM1/2 splicing facilitates isoform‐specific functional analysis in vitro and in vivo. (9th July 2021) - Lin, Jianxiang; Wu, Susu; Shen, Qingmei; Liu, Jie; Huang, Shisheng; Peng, Guangdun; Qiao, Yunbo
Abstract: Objectives: PKM1 and PKM2, which are generated from the alternative splicing of PKM gene, play important roles in tumourigenesis and embryonic development as rate‐limiting enzymes in glycolytic pathway. However, because of the lack of appropriate techniques, the specific functions of the 2 PKM splicing isoforms have not been clarified endogenously yet. Materials and methods: In this study, we used CRISPR‐based base editors to perturbate the endogenous alternative splicing of PKM by introducing mutations into the splicing junction sites in HCT116 cells and zebrafish embryos. Sanger sequencing, agarose gel electrophoresis and targeted deep sequencing assays were utilized for identifying mutation efficiencies and detecting PKM1/2 splicing isoforms. Cell proliferation assays and RNA‐seq analysis were performed to describe the effects of perturbation of PKM1/2 splicing in tumour cell growth and zebrafish embryo development. Results: The splicing sites of PKM, a 5' donor site of GT and a 3' acceptor site of AG, were efficiently mutated by cytosine base editor (CBE; BE4max) and adenine base editor (ABE; ABEmax‐NG) with guide RNAs (gRNAs) targeting the splicing sites flanking exons 9 and 10 in HCT116 cells and/or zebrafish embryos. The mutations of the 5' donor sites of GT flanking exons 9 or 10 into GC resulted in specific loss of PKM1 or PKM2 expression as well as the increase in PKM2 or PKM1 respectively. Specific loss of PKM1 promoted cell proliferation of HCT116 cells and upregulated the expression of cell cycle regulators related to DNA replication and cell cycle phase transition. In contrast, specific loss of PKM2 suppressed cell growth of HCT116 cells and resulted in growth retardation of zebrafish. Meanwhile, we found that mutation of PKM1/2 splicing sites also perturbated the expression of non‐canonical PKM isoforms and produced some novel splicing isoforms. Conclusions: This work proved that CRISPR‐based base editing strategy can be used to disrupt the endogenous alternative splicing of genes of interest to study the function of specific splicing isoforms in vitro and in vivo. It also reminded us to notice some novel or undesirable splicing isoforms by targeting the splicing junction sites using base editors. In sum, we establish a platform to perturbate endogenous RNA splicing for functional investigation or genetic correction of abnormal splicing events in human diseases. Abstract : Because of the lack of appropriate techniques, the specific functions of the two PKM splicing isoforms have not been clarified endogenously yet. In this study, we used CRISPR‐based base editors to perturbate the endogenous alternative splicing of PKM by introducing mutations into the splicing junction sites in HCT116 cells and zebrafish embryos. It's proved that CRISPR‐based base editing strategy can be used to disrupt the endogenous alternative splicing of genes of interest to study the function of specific splicing isoforms in vitro and in vivo